Financial Intermediaries and the Cross‐Section of Asset Returns - ADRIAN, TOBIAS; ETULA, ERKKO; MUIR, TYLER (Journal of Finance, 2014)
ABSTRACT Financial intermediaries trade frequently in many markets using sophisticated models. Their marginal value of wealth should therefore provide a more informative stochastic discount factor (SDF) than that of a representative consumer. Guided by theory, we use shocks to the leverage of securities broker‐dealers to construct an intermediary SDF. Intuitively, deteriorating funding conditions are associated with deleveraging and high marginal value of wealth. Our single ‐factor model prices size, book‐to‐market, momentum, and bond portfolios with an R 2 of 77% and an average annual pricing error of 1%—performing as well as standard multifactor benchmarks designed to price these assets.